BS04. Characteristics of respiratory dysfunction in amyotrophic lateral sclerosis: A clinical study in 159 cases. (May 2018) - Fu, Hanhui; Chen, Jinyi; Shen, Dongchao; Tai, Hongfei; Zhang, Kang; Liu, Shuangwu; Cui, Liying
Abstract : Introduction: Amyotrophic lateral sclerosis(ALS) is a neurodegenerative disorder involving both upper and lower motor neurons with an average survival time of 3–5 years. Respiratory deterioration is the main cause of ALS and affects almost all ALS patients in different courses. Currently, it is still controversial of the characteristics of respiratory deterioration in ALS patients, including the effect of the type of disease onset, as well as the progression rates. Methods: We performed a retrospective cohort study including 159 ALS patients at Peking Union Medical College Hospital from June 2014 to April 2017. Age at symptom onset, sex, time form onset to PFT, ALSFRS-R score, onset and area involved were recorded. All patients were followed in March 2016 and Jun 2017 separately. Depending on the pattern of onset, patents were subdivided into two groups. One included patients with bulbar-onset ALS and the other included those with limb-onset. Results: The mean age at symptom onset of 159 cases included was 52.9 ± 10.1 years old; the male: female ratio was 1.24:1. Bulbar-onset of symptoms was seen in 17.0% patients, while 81.6% presented with limb-onset. The time from symptom onset to PFT was shorter in the bulbar-onset group (7.0 vs. 11.5 m, p = 0.004), as well as the time from symptom onset to diagnosis (8.0 vs. 12.0 m, p = 0.027). Significant differences were showed of the age at symptom onset (p = 0.025), time form symptom onset to diagnosis (p = 0.026) and ALSFRS-R scores (p = 0.004) between the two groups. The PFT parameters revealed a main characteristic restrictive type of dysfunction. Only 26.0% patients of respiratory dysfunction from PFT parameters had respiratory complaints. Mean FVC% and FEV1%value was 86.7% ± 22.2%, 85.6% ± 19.2% respectively. After adjusting for sex, ALSFRS-R score, time from symptom onset to diagnosis, BMI and age at symptom onset, no significant difference was observed for patients with time form symptom onset to PFT less than 14 mouths. In contrast, for those with time more than 14 mouth, bulbar-onset group showed worse PFT values than the limb-onset group, with differences was 27.5% (95%CI: 4.3%, 50.7%), 24.7% (95%CI: 4.3%, 45.2%) and 42.0% (95%CI: 17.7%, 66.4%) separately. The decline rates for FVC% and FEV1% were 0.7% per mouth and 0.8% per mouth. No difference was found between the two groups. Δ FVC% and Δ FEV1% of patients in bulbar-involved group were 1.5% (95%CI: 0.0–18.5%) and 1.4% (95%CI: 0.0–9.8%), which were significantly higher than those in limb-involved group of 0.2% (95%CI: 0.0–10.4) and 0.5%(95%CI: 0.0–8.0%) (p < 0.001, p < 0.001). Conclusion: The main type of pulmonary dysfunction was restrictive pattern. Bulbar involvement predicted poorer respiratory function in ALS patients compared with limb-only involvement, no matter whether the involvement was the onset symptom.The progression rate was higher in the bulbar involved patients than those with limb-only involvement.